2014
DOI: 10.1016/j.msea.2014.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Zircaloy-4 cladding tubes with or without hydride blisters in uniaxial to plane strain conditions with standard and optimized expansion due to compression tests

Abstract: test, which induces a near uniaxial loading, were proposed and developed to reach higher biaxiality ratios (ratio between mechanical quantities in axial and in circumferential direction). The first optimization, named HB-EDC for High-Biaxiality EDC, allowed to reach transverse plane strain conditions. The second optimization, named VHB-EDC for Very High Biaxiality EDC, was designed to reach higher loading biaxiality ratios. These optimized EDC tests were performed * Tel.: +33 1 69 08 39 43; e-mail: arthur.hell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…The stress biaxiality is between 0.6 and 0.95. Efforts are currently underway to develop easy-to-use testing techniques on cladding tubes that cover such loading biaxiality levels [22,12,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress biaxiality is between 0.6 and 0.95. Efforts are currently underway to develop easy-to-use testing techniques on cladding tubes that cover such loading biaxiality levels [22,12,23].…”
Section: Resultsmentioning
confidence: 99%
“…Sugiyama et al [3] results indicated that 60% and 85% of the cladding section was at a temperature lower than 350°C and 480°C respectively at cladding fracture. In laboratory tests that aimed at studying RIA conditions should therefore take into account the temperature level as it affects the material mechanical and thermal behavior [7] and the fracture process [10][11][12], the quantity of dissolved hydrides [13] and the extent of the irradiation recovery [14]. The temperature gradient in the cladding wall is likely one of the thermomechanical loading conditions that is most difficult to reproduce experimentally.…”
Section: Temperaturementioning
confidence: 99%
“…Meanwhile, some slight disparities can still be observed. 6,[22][23][24][25][26] Experimentally, the A-EDC test can achieve a stable uniaxial tension condition in the hoop direction throughout the test. For the other tests, some of them are unable to derive stress-strain relation by experiments.…”
Section: Hoop Stress-strain Relation Derived From A-edc Testsmentioning
confidence: 99%
“…Full-scale in-pile experiments performed in the NSRR or the CABRI reactors [4,5] have shown that, in the case of Zircaloy-4 cladding, the fuel rod can withstand a lower level of deposited energy during the RIA transient when it has a very high burnup, due in particular to hydrogen-induced cladding embrittlement. The mechanical properties of the cladding material depend among other things on hydrogen content, temperature and stress/strain state [3,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the tests currently available reproduce only approximately these features [3,8], which are quite difficult to generate out-of-pile, although some efforts were and are still made to manage it [8,9,14,15,16]. Generally, corrective factors are applied in order to take into account the differences in mechanical loading (biaxiality and strain rate in particular) between separate-effect tests and the actual conditions [12,16].…”
Section: Introductionmentioning
confidence: 99%